UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN PEMBELAJARAN THINK TALK WRITE BERBANTUAN MEDIA GAMBAR PADA SISWA KELAS VI SD NEGERI 1 PURWOSARI - Samsi Samsi (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
The aims of this research were to increase the mathematics result of study by implementation of Think Talk Write (TTW) learning with picture media. The method of the research was Classroom Action Reserach. The instrument of data collection used test. Technique of data analysis used qualitative and quantitative analysis. The research result showed mean the result of study in cycle I is 56,30 and cycle II is 76,10. Then Think Talk Write (TTW) learning with picture media can increase the mathematics result study.